2019
DOI: 10.3389/fpsyt.2018.00760
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Psychiatric Emergency Situations and the Decision-Making Process Leading to Involuntary Admission

Abstract: Introduction: Involuntary admissions to psychiatric hospitals, regardless of their beneficial effects, violate the patients' autonomy. To keep such measures at a minimum and develop less restricting and coercive alternatives, a better understanding of the psychiatric emergency situations which end up in involuntary admissions is needed. This descriptive and exploratory study investigates the consultations leading to involuntary admission and the decision-making process of the referring physicians.Methods: We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Of those, 16 (15%) had referred more than 10 patients involuntarily during this period. The sample is described in more details in another publication elsewhere (Marty et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, 16 (15%) had referred more than 10 patients involuntarily during this period. The sample is described in more details in another publication elsewhere (Marty et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…During the study, we also assessed details on the PES and legal considerations of the referring physicians as well as their compliance with the law. Those are described in detail elsewhere (Hotzy et al, 2019; Marty et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it gives further insight into criteria that are critical to the treatment process of this specific population, such as coercive measures and violence. Given the ethical challenges of involuntary admissions, the findings highlight that both instruments might facilitate more objective evaluations, mitigating potential bias stemming from subjective impressions, time-consuming procedures, and pressure by third parties during the admission process ( 37 , 38 ). Because both instruments do not require a specific training, they could support the evaluation process during an involuntary admission, possibly even for professionals without medical expertise ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had already highlighted the association between physicians' qualifications and coercion rates, showing that limiting the right to require involuntary admission to psychiatrists could reduce the use of compulsion [16]. Another study in Zurich, Switzerland, showed that referring general practitioners found it more difficult to apply legal criteria for involuntary admission and to assess its necessity [72]. GPs also provided the lowest quality commitment certificates [73,74].…”
Section: Discussionmentioning
confidence: 99%